Variation between plant species in pollen digestion rates in the green lacewing Chrysoperla carnea - González, Ezequiel (2022)
Pollen are an important food source for numerous insects and may be used as natural markers in ecological studies. However, to make inferences about the movement rates of insects based on their gut contents, information on pollen digestion rates is needed. Here, we assessed how the consumption and digestion rates of pollen ingested by Chrysoperla carnea Stephens (Neuroptera: Chrysopidae) adults are influenced by plant species, temperature, and sex. We offered pollen of two insect-pollinated plants – Acer pseudoplatanus L. (Sapindaceae) and Helianthus annuus L. (Asteraceae) – and two wind-pollinated plants – Fraxinus excelsior L. (Oleaceae) and Quercus rubra L. (Fagaceae) – differing in size and protein content, to adult lacewings at two temperatures, 20 and 25 °C. After feeding, lacewings were allowed to digest pollen for up to 14 days, sampled at 10 time intervals. At each of these intervals, lacewings were frozen and the internal pollen were obtained through acetolysis and quantified under a light microscope. The number of pollen grains decreased exponentially over time and declined faster for Acer than for the other three plant species. The half-life and the time at which 95% of the pollen grains were digested were lower for Acer than for the other plant species. Lacewings consumed more pollen grains from Acer and Quercus than from Fraxinus and Helianthus. Male lacewings consumed 30% fewer pollen grains than females, but without differences in their digestion rates. Our results show that lacewings consumed higher amounts of high-protein pollen (Acer and Quercus) and that digestion rates differed among plant species, which could be linked to their structural characteristics. The variable digestion rates of pollen grains may influence the study of lacewing diet composition. Studies that make inferences about the pollen diet or movement ecology of lacewings by analysing their gut contents should account for species-specific pollen digestion rates.